Some results involving the parabolic cylinder function - Pittaluga, Giovanna; Sacripante, Laura; Sacripante, Laura (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper is devoted to the study of the modified moments of tbe weight functions x~e-4 (lnxl, p=1.2, on [0 ,00). with respect to the parabolic cylinder function Dv('x). A procedure for a numertcal computation is discussed. Special cases are mentioned.